Proses Islamisasi Nusantara dan proses penyebarannya di Indonesia - Fitriana*, Afifah; Alimni, Alimni; Hanif, Ridwan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Some question that often arise are related to when Islam actually came, where did islam come from, who actually spread Islam to Indonesia for the first time, this article aims to find out the method of early Islamization in the archipelago. The development of the Islamization of Indonesia actually uses three methods, namely. Spread by Muslim traders in a peaceful atmosphere, disseminated by preachers and special guardians from India and Arabia to Islamize the population and increase their knowledge and faith, and deployed with force to fight against pagan goverments. This last method took place soon after an Islamic empire was established in Indonesia where sometimes Islam was spread from there to other areas through war.